Target strength estimates of red emperor (Lutjanus sebae) with Bayesian parameter calibration - Gastauer, Sven; Scoulding, B.; Fässler, S.; Benden, D.; Parsons, Miles (2016)
Red emperor (Lutjanus sebae) is a long-lived tropical demersal snapper which is widely distributed in the Western Pacific and Indian Ocean. Despite the commercial and recreational importance of the species for the Northern Demersal Scalefish Fishery off the Northwest coast of Western Australia, we still lack a thorough understanding of its distribution and abundance in the area. To better understand the acoustic scattering properties of red emperor its acoustic backscattering characteristics were modelled based on swimbladder and body morphology, determined using computed tomography scans. A Kirchhoff-ray mode approximation was coupled with empirical (ex situ) measurements of target strength (TS) obtained from a 38 and 120 kHz split-beam echosounder on board a fishing vessel. Bayesian methods were used for model parameter calibration, which provided uncertainty estimates for some of the TS-model parameters. The derived TS-length relationships were 19.7log 10(L)-75.5 (C.I. 5.9 dB) at 120 kHz and 14.6 log10(L)-64.9 (C.I. 5.8 dB) at 38 kHz. The study demonstrated that small commercial fishing vessels can be used to conduct ex situ experiments and target strength modelling can be effectively based on computer tomography scans. This relatively low cost approach could be applied to other species.